Paz y desarrollo: dos conceptos irreconciliables para las Mujeres Amazónicas del Ecuador (2020)
Peace and Development are two irreconcilable concepts for female leaders and administrators in the northern, central, and southern Amazon of Ecuador. In this context, development is synonymous with neo-extractivism and, therefore, entails the devastation of their territories and ways of life in harmony with nature. In this case, the commodity consensus takes the shape of the constant threat of the South-East Round and the Intercampos Round, through which oil blocks located in their ancestral territories enter into tendering. The Amazon Women Collective —part of the Ecuadorian indigenous movement, but a political subject with its own personality— demands the fulfilment of its mandate. Through direct testimonies from some of the Collective’s members and their mandate, we will come closer to understanding this irresolvable relationship between peace and development, and we will recognize the different forms of violence that this extractive model imprints on their bodies and territories, as a result of their position as defenders of the jungle and as women. In addition, taking the history of the South-East Round as an axis for inquiry, we will address the disputes between the different jurisdictions and territorialities in conflict, which fight to maintain lifestyles in harmony with nature or establish/deepen the prevailing developmental-economicist model.